Respuesta :

SS139

Answer: -601

Step-by-step explanation:

Answer:

-601

Step-by-step explanation:

So first you solve the equations in the parantheses.

8-4= 4 so its going to be

9x3-7x92+4(4)

You are going to multiply 4(4) and get 16

Now it's 9x3-7x92+16

You are going to multiply what needs to be multiplied now so:

9x3= 27 and 7x92=644

So it's:

27-644+16

It doesn't matter whether you do subtraction or addition first, whichever is the first equation so:

27-644= -617 then -617+16= -601